Cost-Effectiveness of Cervical Epidural Steroid Injections: A 3-Month Pilot Study. Issue 2 (April 2019) - Alvin, Matthew D.; Mehta, Vikram; Halabi, Hadi Al; Lubelski, Daniel; Benzel, Edward C.; Mroz, Thomas E.
Study Design: Retrospective cohort. Objectives: There are conflicting reports on the short- and long-term quality of life (QOL) outcomes and cost-effectiveness of cervical epidural steroid injections (ESIs). The present study analyzes the cost-effectiveness analysis of ESIs versus conservative management for patients with radiculopathy or neck pain in the short term. Methods: Fifty patients who underwent cervical ESI and 29 patients who received physical therapy and pain medication alone for cervical radiculopathy and neck pain of <6 months duration were included. Three-month postoperative health outcomes were assessed based on EuroQol-5 Dimensions (EQ-5D; measured in quality-adjusted life years [QALYs]). Medical costs were estimated using Medicare national payment amounts. Cost/utility ratios and the incremental cost-effectiveness ratio (ICER) were calculated to assess for cost-effectiveness. Results: The ESI cohort experienced significant ( P < .01) improvement in the EQ-5D score while the control cohort did not (0.13 vs 0.02 QALYs, respectively; P = .01). There were no significant differences in costs between the cohorts. The cost-utility ratio for the ESI cohort was significantly lower (21 884/QALY gained) than that for the control cohort (176 412/QALY gained) ( P < .01). The ICER for an ESI versus conservative management was negative, indicating that ESIs provide greater improvement in QOL at a lower cost. Conclusions: ESIs provide significant improvement in QOL within 3 months for patients with cervical radiculopathy and neck pain. ESIs are more cost-effective compared than conservative management alone in the shor -term. The durability of these results must be analyzed with longer term cost-utility analysis studies.